Can Practitioners Neglect Theory and Theoreticians Neglect Practice? - Broy, Manfred (Computer (00189162), 2011)
The article states that software engineering is a new field and needs to establish its body of scientific theories, methods, techniques and processes to assist its professionals to attain high levels of quality in software development and maintenance. It is still considered to be a craft being dependent on traditional approaches where it is enough that things work. Recommended is the pursuit of precise terminology, practical and experimental research and evaluation criteria for effectiveness.